Dexamethasone Down-Regulates Expression of Triggering Receptor Expressed on Myeloid Cells-1: Evidence for a TNFα-Related Effect - Mihailidou, Ira; Pelekanou, Aimilia; Pistiki, Aikaterini; Spyridaki, Aikaterini; Tzepi, Ira-Maria; Damoraki, Georgia; Giamarellos-Bourboulis, Evangelos J. (Frontiers in Public Health, 2013)
Objectives To investigate the effect of dexamethasone on triggering receptor expressed on myeloid cells-1 (TREM-1). Methods Lethal infection was induced by Pseudomonas aeruginosa in 96 mice, both wild-type and TNF-/-; mice were pre-treated either with saline or with dexamethasone/hydrocortisone. TREM-1 on neutrophil membranes was measured after sacrifice. Monocytes of the U937 human cell line were challenged by LPS and heat-killed P.aeruginosa with the sequential addition of dexamethasone, hydrocortisone, TNFα and anti-TNF. Expression of TREM-1 and release of soluble TREM-1 (sTREM-1) in supernatants were measured. Results Pre-treatment with dexamethasone prolonged animal survival; this was not shown with hydrocortisone pre-treatment. Mice pre-treated with dexamethasone showed decreased expression of TREM-1 on neutrophils. LPS and P.aeruginosa induced the expression of TREM-1 and the release of sTREM-1 by U937 monocytes; that was decreased upon addition of dexamethasone but not of hydrocortisone. The effect of dexamethasone was enhanced upon addition of TNFα and lost in the presence of anti-TNF. The effect was also lost in TNF-/- mice. Gene expression of TREM-1 by U937 monocytes was decreased after treatment with dexamethasone. Conclusions TREM-1/sTREM-1 is a novel site of action of dexamethasone. This action is related with down-regulation of gene expression and is modulated by TNFα.